ESRA19-0380 Peripheral nerve blocks compared with spinal anaesthesia do not reduce opioid consumption related to initial rebound pain in ankle fracture surgery. (30th August 2019) - Sort, R; Hald, LL; Brorson, S; Nielsen, JK; Hougaard, S; Gögenur, I; Møller, AM
Abstract : Background and aims: Peripheral nerve blocks (PNBs) are increasingly used in limb fracture surgery. However, recent studies suggest that rebound pain when the block wears off may outweigh the benefits on the postoperative pain course. the randomised 'AnAnkle Trial' compared postoperative pain profiles after spinal anaesthesia (SA) and PNB anaesthesia with primary data showing a marked overall benefit with the PNBs on 0–27 hours pain and morphine consumption. We here present secondary outcome data comparing initial rebound pain with PNB versus SA. Methods: Ethically and legislatively approved, randomised, clinical trial with blinded outcome analysis. Adults undergoing primary internal fixation of an ankle fracture were randomised to standardised popliteal sciatic and saphenous PNBs or SA. Postoperative pain regimens were paracetamol, ibuprofen and patient controlled on-demand iv morphine, electronically registered. the patients noted repeated pain scores and time of full return of sensation to the ankle (Ts). the 'rebound' period was predefined as Ts+6 hours. Results: We included 150 patients. Mean block duration was 3.5 hours (3.2–3.9 95%CI) with SA and 16.5 hours (15.8–17.3) for PNBs. Morphine consumption in the rebound period was 18.3 mg (14.6–21.9) with SA and 17.0 mg (13.9–20.1) with PNB ( p= .608, T-test). the mean peak pain scores were 5.6/10 in the SA group and 5.0/10 in the PNB group (p=.136). Conclusions: The immediate rebound pain reaction when the block wears off is not reduced with PNB anaesthesia, despite delaying the onset of postoperative pain for 13 hours.